Occupation: Rainfall [videorecording (Blu-Ray)] - Sparke, Luke; Ewing, Dan, 1985-; Morrison, Temuera; Makoare, Lawrence, 1968-; Gillies, Daniel, 1976- (Saban, 2021)
Two years after aliens land on Earth, survivors from Sydney, Australia, fight in a desperate war as the number of casualties continue to grow.